Evolution of paralell to sub-parallel grabens using analogue and numerical modelling : example of the Pimenta Bueno and Colorado grabens, Parecis Basin, Brazil - Rodrigues, Magda Estrela Oliveira (2021)
Tese (doutorado) — Universidade de Brasília, Instituto de Geociências, Programa de Pós-Graduação em Geologia, 2021.